2014
DOI: 10.1111/dote.12194
|View full text |Cite
|
Sign up to set email alerts
|

Association ofHelicobacter pyloriinfection with esophageal adenocarcinoma and squamous cell carcinoma: a meta-analysis

Abstract: To evaluate the relationship of Helicobacter pylori and cytotoxin-associated gene A (CagA) positive strains with esophageal neoplasm, including esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC), the authors conducted a meta-analysis using a predefined protocol. PubMed, Web of Science, China biology medical literature database, Wanfang, and China National Knowledge Infrastructure were searched for relevant articles from the first available year to April 8, 2013. The fixed or random e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 57 publications
(137 reference statements)
4
69
0
1
Order By: Relevance
“…Moreover, some investigators have claimed that CagA positive H. pylori have an inverse association with esophageal adenocarcinoma (23). The present study has revealed that there was a significant difference between CagA positive and negative H. pylori in patients with some esophageal disorders.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, some investigators have claimed that CagA positive H. pylori have an inverse association with esophageal adenocarcinoma (23). The present study has revealed that there was a significant difference between CagA positive and negative H. pylori in patients with some esophageal disorders.…”
Section: Discussionsupporting
confidence: 56%
“…This has suggested a potential relationship between these two opposing time trends. The most recent meta-analysis to examine the association between H. pylori infection and esophageal adenocarcinoma found an inverse relationship between H. pylori infection and esophageal adenocarcinoma (OR 0.57; 95% CI 0.44–0.73) [ 72 ]. A similar inverse relationship is seen in Barrett’s esophagus [ 73,74 ].…”
Section: Epidemiologic Factorsmentioning
confidence: 99%
“…1). 3, 4, 5, 6 This trend is occurring in other regions as well and EGJ adenocarcinoma (adenocarcinomas that have their epicenter in the 10-cm segment encompassing the 5 cm above and 5 cm below EGJ) constitutes the major burden of GEACs 2 . Selecting appropriate therapy for GEAC may be possible after accurate stage is determined and patients discuss with a multidisciplinary team consisting of medical oncologists, surgeons, radiation oncologists, radiologists, pathologists and supportive care specialists.…”
Section: Introductionmentioning
confidence: 99%